2014
DOI: 10.1080/10408398.2011.654013
|View full text |Cite
|
Sign up to set email alerts
|

Sugar-Fat Seesaw: A Systematic Review of the Evidence

Abstract: Further to reports of a reciprocal relationship between sugar and fat intakes, this review aimed to provide an in-depth

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 51 publications
2
22
0
Order By: Relevance
“…Nutrient analysis revealed that calorie reduction in the formulation was rather insignificant(less than 10%), because the fat proportion increased in the end product. This sugar‐fat seesaw effect has also been shown through a systematic review of dietary intake studies for countries with cultural similarities: United Kingdom, Ireland, other European countries, United States, and Australia (Sadler and others ). This review demonstrated there is a strong and consistent inverse association between total sugars and total fat intakes expressed as percentage energy.…”
Section: Issues With Replacing Added Sugarsmentioning
confidence: 70%
“…Nutrient analysis revealed that calorie reduction in the formulation was rather insignificant(less than 10%), because the fat proportion increased in the end product. This sugar‐fat seesaw effect has also been shown through a systematic review of dietary intake studies for countries with cultural similarities: United Kingdom, Ireland, other European countries, United States, and Australia (Sadler and others ). This review demonstrated there is a strong and consistent inverse association between total sugars and total fat intakes expressed as percentage energy.…”
Section: Issues With Replacing Added Sugarsmentioning
confidence: 70%
“…For instance, in the 1980s and 1990s low-fat diets were frequently recommended to tackle the growing obesity crisis. However, low-fat foods tend to be higher in added sugars, and there is an inverse relationship between the proportion of dietary calories obtained from fat and from sugar (Nguyen, Lin, & Heidenreich, 2016;Sadler, McNulty, & Gibson, 2015). Similarly, herbal tonics are seen as a preferable alternative to animal products but this overlooks the possibility that the plants used may themselves be threatened, for example, species in the genus Coptis are considered an acceptable traditional medicine alternative but at least one is classified as Endangered (Feng et al, 2009;Saha et al, 2015).…”
Section: Success With Alternatives Is Not Guaranteedmentioning
confidence: 99%
“…18 However, only two of the studies examined the relationship in terms of the absolute energy intake derived from sugar and from fat, and both studies showed a positive association. 19,20 The correlation demonstrated (r=0.37) was relatively weak; 20 consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%